Detection of the jaundice-related G71R mutation in the UGT1A1 gene by denaturing high performance liquid chromatography (DHPLC) - Retno Sutomo; Sunartini Hapsara; Suryono Yudha Patria; Hajime Nakamura (Indonesian Pediatric Society, 2009)
Background The G71R mutation in the UGT1A1 gene has beenassociated with neonatal jaundice and other cases of hereditary,unconjugated hyperbilirubinemia in several Asian populations.Currently, DNA sequencing is the only method available toidentify the mutation, which can be time- and labor-intensive,particularly for such projects as population-based genetic studies.A relatively new method, denaturing high performance liquidchromatography (DHPLC), is increasingly used to detect variousmutations.Objective The aim of the present study was to investigate theability of DHPLC to detect the G71R mutation, in comparisonwith the gold standard of sequencing analysis.Methods Seventy-two infants were enrolled. Following genomicDNA extraction, exon 1 of the UGT1A1 gene was amplified bypolymerase chain reaction (PCR). Afterwards, the G71R mutationwas simultaneously, and blindly, determined in all subjects byDHPLC and sequence analysis. The performance of the DHPLCanalysis, compared to the sequence analysis, was assessed in termsof sensitivity and specificity.Results DHPLC detected the G71 R mutation in 31 individuals.Of these, 26 were heterozygous and 5 were homozygous for themutation. This method did not find the mutation in 41 otherindividuals. Sequence analysis produced identical results for allindividuals.Conclusion DHPLC analysis is capable of detecting the G71Rmutation in the UGT1A1 with a degree of sensitivity andspecificity (100% each) that is comparable to sequencing analysis.